Prevalence of, associations with, and prognostic value of tricuspid annular plane systolic excursion (TAPSE) among out-patients referred for the evaluation of heart failure - Kallvikbacka-Bennett, Anna; Dubois-Randé, Jean Luc; Dubos-Rande, Jean-Luc; Damy, Thibaud; Cleland, John G.F.; Kallvikbacka-Bennett, Anne; Goode, Kevin; Khaleva, Olga; Lewinter, Christian; Hobkirk, James; Clark, Andrew; Nikitin, Nikolay P.; et al. (JOURNAL OF CARDIAC FAILURE, 2012)
Background: Prevalence, predictors, and prognostic value of right ventricular (RV) function measured by the tricuspid annular plane systolic excursion (TAPSE) in patients with chronic heart failure (CHF) symptoms with a broad range of left ventricular ejection fraction (LVEF) are unknown. Methods and Results: Of 1,547 patients, mean (±SD) age was 71 ± 11 years, 48% were women, median (interquartile range [IQR]) TAPSE was 18.5 (14.0-22.7) mm, mean LVEF was 47 ± 16%, 47% had LVEF ≤45% and 67% were diagnosed with CHF, defined as systolic (S-HF) if LVEF was ≤45% and as heart failure with preserved ejection fraction (HFPEF) if LVEF was > 45% and treated with a loop diuretic. During a median (IQR) follow-up of 63 (41-75) months, mortality was 34%. In multivariable analysis, increasing age, N-terminal pro-B-type natriuretic peptide (NT-proBNP), New York Heart Association functional class, right atrial volume index, and transtricuspid pressure gradient; lower TAPSE, diastolic blood pressure, and hemoglobin; and atrial fibrillation (AF) or COPD were associated with an adverse prognosis. Receiver operating characteristic curve analysis identified a TAPSE of 15.9 mm as the best prognostic threshold (P =.0001); 47% of S-HF and 20% of HFPEF had a TAPSE of < 15.9 mm. The main associations with a TAPSE < 15.9 mm were higher NT-proBNP, presence of atrial fibrillation and presence of LV systolic dysfunction. Conclusions: In patients with CHF, low values for TAPSE are common, especially in those with reduced LVEF. TAPSE, unlike LVEF, was an independent predictor of outcome. © 2012 Elsevier Inc. All rights reserved.
Batch 008. Output ID 43149.
Keywords: Heart failure; Prognosis; Right ventricle; Echocardiography; TAPSE